Nanomaterials in Optical and Optoelectronic Instrument Making - Борщев, В.Н.; Листратенко, А.М.; Проценко, М.А.; Тымчук, И.Т.; Кравченко, А.В.; Судья, А.В.; Слипченко, Н.И.; Чичков, Б.Н. (Radiotekhnika, 2020)
Search and analysis of results of theoretical and experimental studies on literature and patent sources in the fields of optical and optical-electronic instrumentation is carried out. Current state and development trends of transparent polymer compositions containing nanoscale fillers, which open up new prospects for optical and optical-electronic instrumentation, are considered. Obtained data and recommendations on improvement and creation of new optically transparent nanocomposites are generalized, and can be used not only for connecting components of optical systems, but also for products in scintillation technology, lighting engineering, photovoltaics, and in many other fields of science and technology. Examples of some currently existing polymer and nanopolymer optical systems are considered. They includie an organosilicon composition for connecting optical elements, a plastic scintillator with nanostructured phosphors with improved time characteristics and light output values, a LED with multilayered scatterer with a variable index of refraction and an improved yield of radiation, optical compositions with a high refractive index on high transparency silicones for connection with optical elements in light-emitting devices or for lighting devices with a remote phosphor, as well as new materials and methods for dispersing nanoparticles. Given examples clearly show that complexity of the structures and micro dimensions of modern optical and optoelectronic products for their successful implementation and widespread adoption require new easy-to-use and not expensive optically transparent nanomaterials and technologies for their manufacture.